Pengaruh Financial Strain, Financial Management Behavior, Dan Childhood Consumer Experience Terhadap Financial Satisfaction (Studi Kasus pada Mahasiswa Universitas Islam Malang) - Azizah, Nur Rosyda Dhiya’ul; Mardani, Ronny Malavia; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract All humans have life goals they want to achieve. However, in general, every individual wants a happy life. In the financial aspect, a person can feel happiness when they achieve financial satisfaction. Experience in managing finances will influence individual financial satisfaction. However, most students are currently facing their first experience in managing their own finances without being supervised by their parents. This research aims to find out how much influence financial strain, financial management behavior, and childhood consumer experience have on the financial satisfaction of students at the Islamic University of Malang. This type of research is quantitative with an explanatory research approach. Determining the sample size using the Slovin formula obtained 96 respondents. The sampling technique uses proportionate random sampling by dividing the sample according to the number of students in each department. Data processing uses multiple linear regression analysis with the help of the SPSS version 22 application. The results of this research show that financial strain does not affect financial satisfaction, while financial management behavior and childhood consumer experience have a significant effect on financial satisfaction. Keywords : Financial Strain, Financial Management Behavior, Childhood Consumer Experience, Financial Satisfaction